Differential effects of soil chemistry on the foliar resorption of nitrogen and phosphorus across altitudinal gradients. (25th March 2019) - Gerdol, Renato; Iacumin, Paola; Brancaleoni, Lisa
Abstract: Nutrient resorption from senescing leaves prior to litterfall is a strategy for nutrient conservation in vascular plants. However, the mechanisms through which soil fertility and/or foliar nutrient status affect nutrient resorption are not yet fully known. We used two 1, 000‐m‐wide altitudinal gradients on two different bedrock types (carbonate and silicate) for analysing the interactive effects of temperature and soil chemistry on the resorption efficiency of two major nutrients, nitrogen (N) and phosphorus (P). Our objective was to assess how nutrient resorption varied across the gradients through the adaptation of individual species to changing environmental conditions rather than through changes in species composition. Both N and P resorption efficiency increased across the altitudinal gradients independent of bedrock type. The main process regulating nutrient resorption was a negative feedback to nutrient availability in the soil. The negative feedback of nutrient resorption efficiency to soil nutrient status was unrelated to total soil nutrient contents but depended on concentrations of organic N forms for nitrogen resorption efficiency (NRE) and on inorganic P forms for phosphorus resorption efficiency (PRE), respectively. While we hypothesized that the resorption of P, as a principally rock‐derived nutrient, depended on physical–chemical processes affected by soil chemistry, our results showed that microbial P mineralization was the main source of inorganic P supply to the plants. Both NRE and PRE were effective to improve the growth potential of plants, but there was no evidence of stoichiometric adaptations of N:P RE‐to‐nutrient ratio in the soil. A plain language summary is available for this article. Abstract : Plain Language Summary